The Double Passage of the Intertropical Convergence Zone in Sabah and Sarawak - Camerlengo, Alejandro Livio; Saadon, Mohd Nasir; B. Osman, M. Mahatir (Universiti Putra Malaysia Press, 1998)
The aim of this investigation was to determine the rainfall variability due to the passage of the intertropical convergence zone in East Malaysia. It is shown that the principal (secondary) role of the monthly distribution of precipitation is given by the annual migration of the ITCZ (monsoon winds). In this regard, our investigation is in perfect agreement with a previous study. Other important results of this study are: (i), during the first four months of the year, Sarawak registers considerably more precipitation than Sabah; (ii), the total annual amount of precipitation is maximum in Kuching, decreasing further northwards; and (iii), the annual precipitation pattern of the west coast of Sabah and Sarawak is similar to that of Peninsular Malaysia's east coast.